Elastic spiral triboelectric nanogenerator as a self-charging case for portable electronics. (August 2018) - Kim, Banseok; Chung, Jihoon; Moon, Haksung; Kim, Dongseob; Lee, Sangmin
Abstract: To overcome the limitation of the battery life for portable electronics, the triboelectric nanogenerator (TENG), a new energy harvesting technology in the spotlight, has been demonstrated as a self-charging solution. However, it is difficult to combine TENGs with existing portable devices because of shape differences between the TENG-based charging system and electronic devices. In this study, we successfully developed an elastic spiral triboelectric nanogenerator (ES-TENG) with cylindrical shape connected to a plate. With the flat plate substrate, devices can be attached easily to the plate and ES-TENG can work as a self-powered case accessory. The elastic sheet inside ES-TENG can generate multiple alternating current outputs during both extraction and self-retraction processes. As the elastic sheet is the key to ES-TENG, it is analyzed through dynamic motion of the elastic sheet. Furthermore, we propose fabrication guidelines for ES-TENG, depending on the size of portable electronics and based on the properties of the sheet. We demonstrate the possibility of ES-TENG as a self-charging case accessory that can light 120 white LEDs and power an engineering calculator and a rechargeable Ni-MH battery. Thus, our study is a potential energy harvesting package system for conventional portable electronics. Graphical abstract: fx1 Highlights: A new design of a triboelectric nanogenerator using an elastic spiral sheet is demonstrated. Integrated design between an energy harvesting system and portable electronics is introduced. Design guidelines were studied to maximize the output for elastic spiral TENG. ES-TENG is a potential self-charging/packaging application such as a case accessory for portable electronics.